Exploring the Mechanism of Hawthorn Leaves Against Coronary Heart Disease Using Network Pharmacology and Molecular Docking - Ding, Jie; Wu, Jun; Wei, Haoran; Li, Sui; Huang, Man; Wang, Yan; Fang, Qin (Frontiers in Cardiovascular Medicine, 2022)
Hawthorn leaves, which is a traditional Chinese medicine, has been used for treating coronary heart disease (CHD) for a long time in China. But the limited understanding of the main active compo-nents and molecular mechanisms of this traditional medicine has restricted its application and fur-ther research. The active compounds of Hawthorn leaves were obtained from TCMSP database and SymMap database. The targets of it were predicted based on TCMSP, PubChem, Swiss Target Pre-diction and SymMap database. The putative targets of CHD were gathered from multi-sources data-bases including the Online Mendelian Inheritance in Man (OMIM) database, the DrugBank database, the GeneCards database and the DisGeNet database. Network topology analysis, GO and KEGG pathway enrichment analyses were performed to select the key targets and pathways. Molecular docking was performed to demonstrate the binding capacity of the key compounds to the predicted targets. Furthermore, RAW264.7 cells stimulated by lipopolysaccharides (LPS) were treated with three effective compounds of Hawthorn leaves to assess reliability of prediction. Quercetin, iso-rhamnetin and kaempferol were main active compounds in Hawthorn leaves. 44 candidate therapeu-tic targets were identified to be involved in protection of Hawthorn leaves against CHD. Additional-ly, the effective compounds of it had good binding affinities to PTGS2, EGFR and MMP2. Enrich-ment analyses suggested that immune inflammation related biological processes and pathways were possibly the potential mechanism. Besides, we found that three predicted effective compounds of Hawthorn leaves decreased protein expression of PTGS2, MMP2, MMP9, IL6, IL1B, TNFα and in-hibited activation of macrophage. In summary, the present study demonstrates that quercetin, kaempferol and isorhamnetin are proved to be the main effective compounds of Hawthorn leaves in treatment of CHD, possibly by suppressing expression of PTGS2, MMP2, MMP9, inflammatory cy-tokines and macrophages viability. This study provides a new understanding of the active compo-nents and mechanisms of Hawthorn leaves treating CHD from the perspective of network pharma-cology.